Development of An Inquiry-Based Practicum Guide to Improve Scientific Work Skills and Science Literacy - Achmad Ramadhan; Sutrisnawati Sutrisnawati (Journal of Educational Science and Technology (EST), 2023)
This study aims to develop an inquiry-based laboratory practicum guide and discover the increase in scientific work skills and literacy. The research took place in two stages: the development stage of the practicum guide using the Research and Development (R&D) method and the implementation stage using the research design pretest-posttest control group design. Material experts carry out feasibility testing. The development phase trial was carried out in 2 stages: a small-scale test using ten students and a large-scale test using 30 students. The implementation results were analyzed using the Independent N-Gain score T-test. The assessment results show that the eligibility validation of material experts is 93.38% (excellent). In limited trials, the average value obtained was 90.17% (excellent category), and in the results of large-scale trials, the average value obtained was 95.40% (excellent category). Based on the results Test Independent N-Gain Score, scientific work, and literacy skills obtained Sig. (2-tailed) is 0.00 < 0.05. The author concludes that the results of developing an inquiry-based practicum guide for animal development have met the standards. The developed guide can also improve the scientific work skills and literacy abilities of students who participate in animal development practicums in a meaningful way.